Ethical Implications of Artificial Intelligence in Health Communication Practice in Nigeria - Chinelo Ebele Uchendu; Mmesomachukwu Chukwuemeka Iloh; Carol Dixon Odoyi; Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR) Publisher, 2026)
Artificial intelligence (AI) is increasingly shaping the landscape of health communication by transforming the ways health information is generated, distributed, and consumed. In Nigeria, the integration of AI-driven technologies such as chatbots, automated health information systems, predictive analytics, and algorithm-based content dissemination has created new opportunities for improving public health communication and expanding access to health information. However, the rapid adoption of these technologies also raises significant ethical concerns that require critical scholarly attention. This paper provides a conceptual examination of the ethical implications of AI in health communication practice in Nigeria. Based on the existing literature on digital communication, health communication, and technology ethics, the paper explores key ethical issues including data privacy and protection, algorithmic bias, misinformation and disinformation, transparency and accountability, and the digital divide. The paper argues that while AI has the potential to enhance the efficiency, reach, and personalization of health communication, the absence of robust ethical guidelines and regulatory frameworks may undermine public trust and exacerbate existing health inequalities. In the Nigerian context, where disparities in digital literacy and access to technology remain pronounced, the ethical deployment of AI becomes even more critical to ensure that vulnerable populations are not marginalized in the process of technological innovation. The paper therefore advocates for the development of context-specific ethical standards, stronger regulatory oversight, and interdisciplinary collaboration among communication scholars, health professionals, policymakers, and technology developers. Such measures are necessary to ensure that the application of AI in health communication aligns with principles of equity, responsibility, and public interest.